2018
DOI: 10.1080/02626667.2018.1472379
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and land management effects on erosion and soil properties in traditional Brazilian tobacco plantations

Abstract: No-tillage and inter-crops have been progressively introduced into traditional Brazilian tobacco plantations. However, there is a lack of information about their impact on soil erosion rates and soil properties. We studied 10 experimental plots in Paraná (Brazil) that rotated from no-tillage tobacco to two different inter-crop types (black beans and oats) and conventionally tilled tobacco to quantify erosion rates from September 2014 to February 2016. The results show that soil loss (18 Mg ha −1 ) and runoff c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…The cultivation of tobacco also demands land with uncovered soil. It is cultivated in September, after the coldest months, in attempt to benefit from the natural hot and regular rainfall (it does not need irrigation in this part of the world) [39], although the highest soil erosion rates have been detected in summer during the harvesting period [40].…”
Section: Discussionmentioning
confidence: 99%
“…The cultivation of tobacco also demands land with uncovered soil. It is cultivated in September, after the coldest months, in attempt to benefit from the natural hot and regular rainfall (it does not need irrigation in this part of the world) [39], although the highest soil erosion rates have been detected in summer during the harvesting period [40].…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of forty years of stemflow and throughfall studies, we observed several objectives, including understanding the hydrological process (Levia Jr. and Frost, 2003;Dugas, 1990); soil erosion (Zheng et al, 2019;Antoneli et al, 2018), soil water balance (Canone et al, 2017), the transfer of contaminants (Ranalli and Macalady, 2010), and others. However, in a scenario of global climate change (Pachauri et al, 2014), stemflow and throughfall research in agricultural areas has become more important than ever, or at least the data needs to be revised in the face of new climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The most interesting of this system is to understand how local farmers use their water (usually permanent streams and rivers) in farms aimed at extensive livestock husbandry in areas where water shortage is not common. Finally, we have to emphasize that faxinals are competing for surface water with large commercial cultivations of tobacco leaves that are also frequent in Prudentópolis [18].…”
Section: Study Casesmentioning
confidence: 99%